Computational analysis of the radial mechanical performance of PLLA coronary artery stents. Issue 1 (January 2015) - Pauck, R.G.; Reddy, B.D.
Abstract Stents have been an effective tool to restore and maintain the patency of narrowed blood vessels, but they must have sufficient radial strength. Biodegradable stent materials have substantially lower mechanical properties than permanent stents. The stent geometry and material properties must be considered simultaneously when assessing stent performance. Material tests were performed to determine the mechanical characteristics of high-molecular-weight poly-l-lactic acid (PLLA). The results were used to calibrate an anisotropic elastic-plastic material model. Three distinct geometries were analysed with a range of material stiffness values in a finite element analysis to investigate their comparative effect on the radial strength, recoil, and radial stiffness. The performance of the different geometries varies substantially, with one particular geometry, with the highest material stiffness of 9 GPa, exceeding the desired radial strength of 300 mmHg.